Report of the Special-purpose Committee on Names of Fungi with the Same Epithet, established at the XIX International Botanical Congress in Shenzhen, China - James K. Mitchell; David L. Hawksworth; Shaun R. Pennycook (IMA Fungus)
Abstract A Special-purpose Committee on Fungal Names with the Same Epithet was established at the XIX International Botanical Congress (IBC) in Shenzhen, China in 2017, with a mandate to report to the 12th International Mycological Congress (IMC) with recommendations on a preferred course of action with respect to names of pleomorphic fungi sharing the same epithet under the International Code of Nomenclature for algae, fungi, and plants. This report provides a synthesis of the deliberations from the Special-purpose Committee. We discuss the arguments for and against the proposed solution to the problems that have arisen regarding the nomenclature of fungi described in multiple morphs using the same epithet. We also propose a gentler method of addressing the problem using existing procedures.